2021
DOI: 10.1039/d1sc00965f
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing a three-center single-electron metal–metal bond in a fullerene cage

Abstract: Trimetallic carbide clusterfullerenes (TCCFs) encapsulating a quinary M3C2 cluster represent a special family of endohedral fullerenes with open-shelled electronic configuration. Herein, a novel TCCF based on a medium-sized rare earth...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…Considering that the 4f electrons of lanthanide atoms are usually not involved in the chemical bonding of metallofullerenes, we employed ECPnMWB (n is the number of core electrons) with 4f-in-core effective core potentials and the corresponding valence basis sets for the lanthanide atoms. In a recent work by Popov and coworkers, 39 the results of DFT calculations on Dy 3 C 2 @C 80 with a similar 4f-in-core treatment are consistent with the experimental results, confirming the reliability of such a calculation method. For geometry optimization, the 6-31G(d) basis set 40 was used for the carbon atom.…”
Section: Computational Detailssupporting
confidence: 73%
See 2 more Smart Citations
“…Considering that the 4f electrons of lanthanide atoms are usually not involved in the chemical bonding of metallofullerenes, we employed ECPnMWB (n is the number of core electrons) with 4f-in-core effective core potentials and the corresponding valence basis sets for the lanthanide atoms. In a recent work by Popov and coworkers, 39 the results of DFT calculations on Dy 3 C 2 @C 80 with a similar 4f-in-core treatment are consistent with the experimental results, confirming the reliability of such a calculation method. For geometry optimization, the 6-31G(d) basis set 40 was used for the carbon atom.…”
Section: Computational Detailssupporting
confidence: 73%
“…For C 80 -based clusterfullerenes containing three metal atoms, such as M 3 N@C 80 , 19 M 3 C 2 @C 80 , 39,48 Sc 3 CH@C 80 10 and Ti 3 C 3 @C 80 , 49 it is generally accepted that the encapsulated cluster transfers six electrons to the fullerene cage. On the other hand, for trimetallofullerenes without any non-metal mediator, such as Y 3 @C 80 21 and Er 3 @C 74 , 25 the inner metal atoms are also thought to donate six electrons in total to the outer cage.…”
Section: Stability Of Ln@c 80mentioning
confidence: 99%
See 1 more Smart Citation
“…A fascinating ability of endohedral metallofullerenes (EMFs) to stabilize metal clusters with unusual valence and spin state opens access to new aspects of molecular and electronic structure, in particular for lanthanides and actinides. But EMFs with unconventional valence states of endohedral metals are not always chemically stable in their pristine form, which complicates their extraction from a fullerene soot and further isolation. Acquiring such EMFs may then require their transformation into a more stable state, often achieved by a redox process or a chemical functionalization. …”
Section: Introductionmentioning
confidence: 99%
“…For trimetallic carbide clusterfullerenes (TCCFs), very recently, Jin et al found that, in Dy 3 C 2 @I h (7)-C 80 , a three-center-one-electron (3c−1e) Dy−Dy−Dy bond is formed. 22 In this case, the Dy 3 C 2 cluster presents a bat ray configuration with the C 2 unit elevated with respect to the Dy−Dy−Dy plane. This is different from the nearly planner and trifoliate configurations for the inner cluster found in Sc 3 C 2 @C 80 and its singly bonded derivative, respectively.…”
Section: ■ Introductionmentioning
confidence: 97%